Morphological Study for some species of the genus Onobrychis Mill. From the family Papilionaceae - Athiya N. Al-Mashhadani; Zainab Jawad Amer (Journal of Madenat Alelem University College, 2015)
The current research included Palynological study for eleven taxa of the genus Onobrychis Mill. Family Papilionaceae. The study included measurement the dimension of pollen grains and there shape in polar and equatorial views and measuring thickness wall of the pollen grain also including configuration of the wall surface . The study showed that there are variation in pollen grains characters for the studied taxa.